PERLINDUNGAN HUKUM TERHADAP DEBITOR YANG TELAH DIJATUHI PUTUSAN SERTA MERTA DALAM KEPAILITAN - ASTRI ESTER SILALAHI (PREMISE LAW JURNAL, 2015)
Immediate verdict is decision which can be executed although it has not had any legal force which is final and conclusive (inkracht van gewijsde). The implementation of immediate verdict should be based on the prevailing regulations in order to forestall new problems as the result of the implementation of the immediate decision itself. The formulas of the problem were as follows: how about the immediate decision in Law on Bankruptcy, how about legal protection for debtors who had immediate decision imposed upon him in Law on Bankruptcy, and how about the consideration of the Constitutional Court on Judicial Review No. 144/PUU-VII/2009. The research used judicial normative, using primary, secondary, and tertiary legal materials. The data were analyzed qualitatively by conducting library research. Keywords: Immediate Decision, Debtor, Bankruptcy